Purification of L-asparaginase through supported ionic liquid - Nunes, João C. F. (2023)
L-asparaginase (ASNase) is an amidohydrolase enzyme applied as an anticancer agent in lymphoproliferative disorders treatment, as an acrylamide reduction agent in starch-rich foods cooked at high temperatures, and as a L-asparagine biosensor. ASNase is widely distributed in nature, e.g., microorganisms, plants and tissues of several animals. Nevertheless, most commercial ASNase are from recombinant microorganisms, whose production can be performed by fermentation. However, its purification accounts for up to 80% of total production cost. Hence, a novel cost-effective purification process is of emerging concern to allow its widespread use. The main goal of this work was to develop a novel cost-effective purification process for ASNase from complex recombinant Bacillus subtilis cell extract obtained by ultrasound sonication. Silica-based supported ionic liquid-like phase (SSILLP) materials comprising quaternary ammonium and chloride as counterions were assessed as cost-effective ASNase purification supports using a simple adsorption method. An initial screening was performed to identify the most promising SSILLP material for the purification of ASNase. Specific purification conditions, e.g., medium pH and solid/liquid ratio, were optimized through Response Surface Methodology. Semi-continuous purification of ASNase was carried out under the optimized purification conditions, which enabled an increase in the purification factor. Through this approach, process costs, energy consumption, and waste produced, might be reduced, leading to the enzyme price decrease, thereby enabling its wider application.